Serum Fibronectin Levels Increased Significantly Following the Administration of an Inactivated SARS-CoV-2 Vaccine: A Prospective Observational Study - Zhao, Bennan; Kang, Jun; Du, Qing; Liu, Dafeng (International journal of general medicine, 2025)
There has been a lack of comprehensive studies on the long-term observation of laboratory values following the administration of SARS-CoV-2 vaccines. The objective of this study is to assess the long-term impact of inactivated SARS-CoV-2 vaccines on coagulation function and other health indicators. We enrolled residents of Chengdu who consented to receive inactivated SARS-CoV-2 vaccines, categorizing them into two groups: healthy donors (n=40) and survivors of COVID-19 infection (n=34), based on their SARS-CoV-2 infection status prior to vaccination. Blood samples from the subjects were collected at specific intervals following vaccination. The levels of Fibronectin (FN) increased significantly in both healthy donors and survivors of COVID-19 infection after receiving two doses of the inactivated SARS-CoV-2 vaccine (both P < 0.001), and there was no statistically significant difference in the degree of FN increase between the two groups (153.05 ± 77.19 mg/L vs 172.32±90.42 mg/L, P=0.326). The rate of elevated FN levels was significantly higher six months after vaccination compared to the rate before vaccination, both in healthy donors (85.0% vs 5.0%, P<0.001) and in survivors of COVID-19 infection (94.1% vs 29.4%, P<0.001). Additionally, the levels of FN in healthy donors further increased six months after receiving a booster dose of the inactivated vaccine compared to pre-booster levels (569.90±119.44 mg/L vs 467.35±62.04 mg/L, P < 0.001). The study indicates that serum FN levels increased significantly following the administration of the inactivated SARS-CoV-2 vaccine, and these elevated FN levels may persist for more than six months. However, it remains unclear whether this increase could result in any adverse effects.